Eksplorasi Cerita Rajapala Sebagai Inspirasi Dalam Penciptaan Seni Lukis Komik Digital - Aryandika, Made; Gulendra, I Wayan; Mudana, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
Rajapala's story is a symbol of the love and escaptic marriage between man and angel. The message that can be gleaned from this story or literary work is "do not seek pleasure by means of bulus wit or akompli nature like I King pala against the angel Ken Sulasih". Therefore the author became inspired to do the writing and embodiment entitled "Exploration Rajapala Story As Inspiration In The Creation Of Digital Comic Painting". Afterwards by examining the message and meaning of Rajapala's story, the author was inspired to create a storyline with the embodiment style of the author that they re-authored rajapala story based on the theoretical approach of the book "Making Comics", Scott McCloud. Not to forget also the author uses elements of digital comic painting so that in the creation effort can run well. Therefore, the creation of digital comics writers use the method of creation of digital comic painting works, namely exploration, experimentation, and formation so that digital comic art can be created. The creation of rajapala digital comics is an attempt to explore of Rajapala's story.